Can personality traits affect detention length in a forensic institution? - Margetić, Branimir; Aukst Margetić, Branka; Ivanec, Dragutin (2014)
The aim of the study was to assess whether the patients’ personality traits may predict the length of current detention. A cross-sectional analysis was conducted in 56 male forensic in-patients with schizophrenia spectrum disorders. Patients were assessed by means of the Temperament and Character Inventory and the Positive and Negative Syndrome Scale (PANSS). Regression analysis has suggested that the character dimension, cooperativeness, and the type of offense were predictors of duration of current detention. Results suggest that information about the patients’ personalities may be helpful in better understanding and/or predicting the patients’ behaviors.